From gender bias to gender awareness in medical education - Verdonk, Petra; Benschop, Yvonne W. M.; de Haes, Hanneke C. J. M.; Lagro-Janssen, Toine L. M. (Advances in Health Sciences Education, 2009)
Gender is an essential determinant of health and illness. Gender awareness in doctors contributes to equity and equality in health and aims towards better health for men and women. Nevertheless, gender has largely been ignored in medicine. First, it is stated that medicine was ‘gender blind’ by not considering gender whenever relevant. Secondly, medicine is said to be ‘male biased’ because the largest body of knowledge on health and illness is about men and their health. Thirdly, gender role ideology negatively influences treatment and health outcomes. Finally, gender inequality has been overlooked as a determinant of health and illness. The uptake of gender issues in medical education brings about specific challenges for several reasons. For instance, the political-ideological connotations of gender issues create resistance especially in traditionalists in medical schools. Secondly, it is necessary to clarify which gender issues must be integrated in which domains. Also, some are interdisciplinary issues and as such more difficult to integrate. Finally, schools need assistance with implementation. The integration of psychosocial issues along with biomedical ones in clinical cases, the dissemination of literature and education material, staff education, and efforts towards structural embedding of gender in curricula are determining factors for successful implementation. Gender equity is not a spontaneous process. Medical education provides specific opportunities that may contribute to transformation for medical schools educate future doctors for future patients in future settings. Consequently, future benefits legitimize the integration of gender as a qualitative investment in medical education.
Keywords: approches et analyses; discipline; europe; formation des médecins; médecine; pays-bas; projet charge mentale; rapports sociaux de sexe; régions géographiques; santé; sciences; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques; éducation

La grande arnaque : sexualité des femmes et échange économico-sexuel - Tabet, Paola (Bibliothèque du féminisme, 2004)
Dans la majorité des sociétés connues, la sexualité apparaît comme un échange asymétrique et non réciproque entre hommes et femmes, une compensation masculine pour une prestation féminine, un paiement qui peut revêtir les formes les plus variées en échange d'une sexualité transformée en service. Comment se fait-il que les hommes, même plongés dans les situations les plus misérables, peuvent se payer le service sexuel d'une femme - alors que non seulement les femmes n'ont pas, sauf exception, cette possibilité mais de plus n' ont même pas droit à leur propre sexualité ?
Keywords: EDI; approches et analyses; cours; cycles supérieurs; discipline; division sexuelle du travail; ethnologie; fem1000; fem7000; inégalités; lit3220; premier cycle; rapports sociaux de sexe; sciences; sciences humaines; sexualité; systèmes d'oppressions; thématiques; épistémologie

Woman: An intimate geography - Angier, Natalie (Anchor Books, 2000)
Woman is a fascinating, fact-filled guide that covers everything from organs to orgasms, hormones to hysterectomies. With her characteristic clarity, insight, and sheer exuberance of language, bestselling author Natalie Angier cuts through the still-prevalent myths and misinformation surrounding the female body, that most enigmatic of evolutionary masterpieces. With a witty and assured narrative, and a reader-friendly dose of science, Woman is an essential and engaging resource for all time.
Keywords: amériques; approches et analyses; biologie; corps; cours; différence des sexes; discipline; fem1000; médecine; premier cycle; psychologie; rapports sociaux de sexe; régions géographiques; santé; sciences; sciences humaines; stéréotypes; thématiques; états-unis

L'invention du naturel : les sciences et la fabrication du féminin et du masculin - Gardey, Delphine; Löwy, Ilana.. (Histoire des sciences, des techniques et de la médecine, 2000)
Comprendre ce que sont les hommes et les femmes, penser la différence entre les sexes a constitué et constitue encore un objet d'investigation et un enjeu politique et social de premier ordre. Des sciences d'hier à celles d'aujourd'hui, des discours et des pratiques médicales aux plus récentes sciences humaines, les auteurs de cet ouvrage révèlent la fragilité des évidences dites sur la nature ou le corps des femmes et des hommes, et insistent sur la force des arrangements et organisations du social qui ont pu en découler. Plus qu'une enquête descriptive sur les états variables des représentations proposées par les sciences, il s'agit d'analyser comment les scientifiques " en société " élaborent les critères de différenciation entre les sexes, contribuant à faire endosser à la nature certaines formes de domination. Convié à découvrir, en France et à l'étranger, l'histoire récente de ces nouveaux terrains d'enquête, le lecteur est aussi invité à méditer sur les effets de longue durée d'une modernité occidentale instaurée sous le signe de l'altérité entre raison et nature, hommes et femmes.
Keywords: approches et analyses; cours; discipline; discours dominant; essentialisation; genre; histoire et politique; identité sexuelle; naturalisation; premier cycle; production des savoirs; rapports sociaux de sexe; sciences; sciences humaines; sciences sociales; sex3383; sexe/genre; sociologie; systèmes d'oppressions; thématiques; épistémologies féministes